Application of information technology (it): Evidence from manufacturing SMEs in Vietnam - Vu, Hoang Nam (Journal of International Economics and Management, 2014)
In Vietnam, small and medium sized enterprises (SMEs) account for a large proportion in terms of both number of enterprises and number of jobs created. Despite the fact that information technology is widely acknowledged to play an increasingly important role in an ever modern business environment, SMEs are often considered to have weak capacity in applying information technology in doing their businesses. Based on data from an SME survey conducted in Vietnam in 2011, this study shows that human resources,formality of the SMEs, and physical infrastructureare the key determinants of their application of information technologyandperformance.